A recyclable adsorbent for salinized groundwater: Dual-adsorbent desalination and potassium-exchanged zeolite production. (October 2018) - Gibb, Nick P.; Dynes, James J.; Chang, Wonjae
Abstract: This study focused on advancing the dual-adsorbent desalination technique that sequentially combines calcined layered double hydroxide (CLDH) and acid-treated zeolites (H-form zeolite) using groundwater spiked with potash mining effluent (brine). In sequential batch experiments, the CLDH adsorbent first reduced the high Cl − concentration (4600 mg/L) of saline groundwater by 96%, the Ca 2+ by 90%, and the Mg 2+ by 92%, while transiently raising the pH to 12.80. H-form zeolites preconditioned with Na + then removed 92% of the Na + (2010 mg/L), while neutralizing the adsorption effluent pH to 7.7 and lowering the sodium adsorption ratio (SAR; 139.6 to 6.6) and the hardness (574 to 48.4 mg/L). In comparison, an equivalent amount of unmodified zeolite removed only 51% of the Na + and generated extremely hard water due to Ca 2+ and Mg 2+ release (1519 mg/L). Na + -conditioning the zeolites prior to acid treatment enhances native cation removal, forming H-form zeolites. Synchrotron-based X-ray scanning transmission microscopy (STXM) showed the occurrence of dealumination and visualized the sodium distribution associated with Si and Al sites in the H-form zeolites. Four consecutive desalination cycles were feasible for Na + and K + adsorption by regenerating the H-form zeolite. During regeneration, the Na + desorbed while the K + remained in the regenerated zeolites. Cumulative K + loading in the regenerated zeolites increased from 4.8 to 21.2 mg/g, producing K-form zeolites. These K-form zeolites released K + (2.15 mg/L for 24 h) in a leaching test and could potentially be considered as nutrient-supply media in other applications, thereby recycling the spent zeolites after multiple desalination treatments. Highlights: CLDH and H-form zeolite remove Cl − and Na + from potash brine-spiked groundwater. Na + -preconditioning and acid treatment of zeolites produce purer H-form zeolites. Synchrotron-based STXM showed dealumination and Na + abundance in H-form zeolites. It is feasible to regenerate the H-form zeolite for multiple Na + -removal cycles. H-form zeolite is converted to useful K-form zeolite after desalination cycles.